PEMBERDAYAAN MASYARAKAT MELALUI EDUKASI PENGOLAHAN PROPOLIS KELOMPOK SAPO BEN BEN DESA BATU JONG JONG KECAMATAN BAHOROK - Yayuk Yuliana; Yayuk Putri Rahayu; Diana Sopha; Muhammad Arif; Oca Putri Nazuhra (LP2M STP Mataram, 2024)
The problem faced by the people of Batu Jong Jong village is the lack of knowledge about the use of bee glue or what is known as raw propolis. The aim of this service is to make it easier for people to process raw propolis, which is something that needs to be understood and understood. The method used in this service is by conducting education or education, surveys by administering questionnaires for pre-test and post-test to measure initial abilities, level of understanding of knowledge about propolis, providing socialization and training. Results: 85.71% of the village community already understands the knowledge about the use of propolis processing as a potential natural resource in Batu Jong Jong village, Bahorok District